The Effect of Storage Duration on the pH Stability and Reducing Sugar Content of Liquid Cane Sugar with Brix Concentrations of 65, 66, and 67 Under Room Temperature and Refrigerated Conditions - Mahesa Putra Dwi Pamungkas (CV. Publikasi Indonesia, 2026)
Cane liquid sugar is a form of cane sugar derivative products that are processed through a series of stages, ranging from extraction, refining, to evaporation to obtain a sugar solution with a certain concentration. However, liquid sugar is easily damaged during storage, so it is necessary to carry out a shelf life analysis to ensure product safety and quality. This study aims to determine the effect of the long storage of sugarcane liquid sugar with the concentration of Brix 65, 66, and 67 on the stability of pH and Reducing sugar at room and refrigerator temperature conditions. Samples of cane liquid sugar were stored in 100 ml borosilicate glass bottles for 30 days and then pH and sugar reduction tests were carried out on day 0, day 7, day 14, day 21, and day 30. The results showed that the longer the storage, the more significant changes occurred in the pH and Reducing sugar levels, with the refrigerator storage temperature being more able to maintain stability than the room temperature. Higher Brix concentrations provide better stability to such changes. The longer the storage, the lower the pH and the more the reducing sugar will increase.